2022
DOI: 10.2147/ppa.s381937
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus Between Physician-Patient Communication and Health Outcomes: Level of Patient Communication Satisfaction and Its Impact on Adherence in Ethiopian Comprehensive Specialized Hospitals

Abstract: Introduction This study aims at assessing the level of patient communication satisfaction and its impact on patient adherence among public hospitals in Ethiopia. Methods The study employed a cross-sectional design. Data were obtained using Communication Assessment Tool (CAT) and the Adherence to Refills and Medication Scale (ARMS) administered to 381 patients asking them to evaluate satisfaction with physician-patient communication and report their level of adherence re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…This could be explained by married people being more likely to be guarded and have better medication adherence. 43 , 44 In addition, tumor size, the mitotic index, and location were all identified as principal determiners, which is in line with the wide recognition of their significance. 45 Cutoff values for tumor size and the mitotic index were decided according to the NCCN guidelines.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This could be explained by married people being more likely to be guarded and have better medication adherence. 43 , 44 In addition, tumor size, the mitotic index, and location were all identified as principal determiners, which is in line with the wide recognition of their significance. 45 Cutoff values for tumor size and the mitotic index were decided according to the NCCN guidelines.…”
Section: Discussionsupporting
confidence: 67%
“…Married individuals were likely to get a better prognosis as per our findings. This could be explained by married people being more likely to be guarded and have better medication adherence 43,44 . In addition, tumor size, the mitotic index, and location were all identified as principal determiners, which is in line with the wide recognition of their significance 45 .…”
Section: Discussionsupporting
confidence: 54%
“…Previous research has suggested that communication moderates the process of "allowing feelings to flow" between patients and physicians (60). Good communication can reduce the patient's pain experience, lower the cost of care, and help the patient recover more quickly, thus promoting greater patient satisfaction (61). In the present study, we found that patients felt it was more important for medical staff to state the problem clearly and promptly (B = 0.82, p < 0.01), to respond to the patient's needs (B = 0.82, p < 0.01), and for the patient to understand the information (B= 0.92, p < 0.01).…”
Section: Sa5mentioning
confidence: 99%
“…During their education, HCPs undergo communicative skills training, including topics such as communication function, building relationships, gathering information, providing information, making decisions, responding to emotions, managing uncertainty, and enabling patient self-managing [ 5 ]. Extensive research shows that these skills are frequently unsatisfactory when assessed in clinical practice [ 6 ] and from the patients' perspective [ 7 , 8 ]. Some examples involve missed opportunities by the HCP to show empathy or to start a relevant discussion with the patient [ 9 ].…”
Section: Introductionmentioning
confidence: 99%